(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
Diabetic nephropathy is a specific pathological change in the renal vessels that occurs in diabetes mellitus. This complication leads to glomerulosclerosis, reduces renal filtration function, and contributes to the development of chronic renal failure (CRF). Clinically, diabetic nephropathy is manifested by proteinuria and microalbuminuria, nephrotic syndrome, arterial hypertension, signs of uremia, and CRF. Diabetic nephropathy is one of the most severe complications of both type 1 and type 2 diabetes mellitus. It manifests in the late stages of the disease and is a leading cause of death. Diabetic nephropathy is diagnosed in 10-20% of patients with diabetes. The peak development of diabetic nephropathy occurs 15-20 years after the onset of diabetes. The results of our study suggest that metabolic, hemodynamic, and genetic factors play a significant role in the development of diabetic nephropathy in patients with type 2 diabetes in the study group.